Active fault control based on interval observer for discrete-time linear switched systems - Marouani, Ghassen; Nguyen, Dang Khai; Dinh, Thach Ngoc; Raïssi, Tarek (European journal of control, 2024)
This paper presents a comprehensive investigation on active fault tolerant control (AFTC) for discrete-time switched systems subject to disturbances and known switching signals. The proposed approach employs interval observers in a two-step implementation strategy. Firstly, a fault detection and isolation (FDI) module based on interval observers is introduced to estimate actuator faults affecting the switched system. In order to enhance the accuracy of this module, an L∞ criterion is utilized. Secondly, a feedback control law is designed to compensate the impact of actuator faults. The controller parameters are determined by solving linear matrix inequalities (LMI). The effectiveness of the proposed AFTC scheme is demonstrated through extensive analysis and simulation studies.